Using technology to find out about the world. (2nd July 2021) - Hewson, Claire
Abstract : Each day technology helps us to build more knowledge, from laboratory equipment to search engines. As children are growing up in a digital age it is vital to incorporate technology as part of their everyday discovery of the world around them.